Homepage template for academic / Sho Hock Chuan - Sho, Hock Chuan (2002)
With the tremendous growth of the Internet and the expansion of the World Wide Web, homepage has become the target of academics to explore in web design and development, sharing information, published articles, etc. Homepage Template for Academic (HTFA) is a system developed for academics to configure and set up their homepage according to their own need by developing a webbased template. HTF A allows academics to build a homepage without any code writing, the layout and the format of homepage already set up in the template their choose according to their need. The template built will be convenient to academics because they do not have to spend much time to set up their homepage design and do coding. HTFA will lead academician to the era of homepage development and design. The project objective is to provide convenience, accessibility, free and quality interactive service for homepage builder. Besides that, towards the paperless technology, academician are encouraged to publish up their lecture notes, tutorials, articles, assignment/projects on the web. HTFA allows academics login to the system with their user identity and password. Academics can download web templates, create homepage, edit existing pages, updated files and upload files in the system. Prototyping model is the development model chosen for develops the HTFA system because it is a tool for helping developers lay out what they need to do and provide the potential for changing the system early in its development. Tools such as the Hypertext Markup Language (HTML), Active Server Pages (ASP), JavaScript, VBScript, Microsoft FrontPage, SQL Server 7.0 and etc were chosen for implementation capability and ease to use.